Continuous function of 80 primary renal allografts for 30–47 years with maintenance prednisone and azathioprine/mycophenolate mofetil therapy: A clinical mosaic of long‐term successes. Issue 1 (27th November 2020) - Braun, William E.; Herlitz, Leal; Li, Jianbo; Schold, Jesse; Poggio, Emilio; Stephany, Brian; Fatica, Richard; Nally, Joseph; Brown, Kathleen; Fairchild, Robert; Baldwin, William; Goldfarb, David; et al.
Abstract: Eighty primary renal allograft recipients, 61 living‐related and 19 deceased donor, transplanted from 1963 through 1984 had continuous graft function for 30–47 years. They were treated with three different early immunosuppression programs (1963–1970: thymectomy, splenectomy, high oral prednisone; 1971–1979: divided‐dose intravenous methylprednisolone; and 1980–1984: antilymphocyte globulin) each with maintenance prednisone and azathioprine, and no calcineurin inhibitor. Long‐term treatment often included the anti‐platelet medication, dipyridamole. Although both recipient and donor ages were young (27.2 ± 9.5 and 33.1 ± 12.0 years, respectively), six recipients with a parent donor had >40‐year success. At 35 years, death‐censored graft survival was 85.3% and death with a functioning graft 84.2%; overall graft survival was 69.5% (Kaplan–Meier estimate). Biopsy‐documented early acute cellular and highly probable antibody‐mediated rejections were reversed with divided‐dose intravenous methylprednisolone. Complications are detailed in an integrated timeline. Hypogammaglobulinemia identified after 20 years doubled the infection rate. An association between a monoclonal gammopathy of undetermined significance and non‐plasma‐cell malignancies was identified. Twenty‐seven azathioprine‐treated patients tested after 37 years had extremely low levels of T1/T2 B lymphocytes representing a "low immunosuppression state of allograft acceptance (LISAA)". The lifetime achievements of these patients following a single renal allograft and low‐dose maintenance immunosuppression are remarkable. Their success evolved as a clinical mosaic.